WORKSHOP PENINGKATAN KUALITAS SDM BAGI CALON GURU FISIKA MELALUI MEDIA PRAKTIKUM KOMPONEN ELEKTRONIKA PASIF DAN AKTIF - Kurriawan Budi Pranata; Chandra Sundaygara; Muhammad Sayadi; Sholikan Sholikan Sholikan; Hari Wijaya; Muhammad Ghufron (STKIP Persada Khatulistiwa Sintang, 2020)
: Prospective physics teachers are the seeds of the next generation to spread science. But the understanding of science has been balanced with standard laboratory facilitation. In fact there are still many public and private schools that do not have adequate laboratory facilities. Whereas a physics teacher candidate must be able to teach in all fields and conditions. This is a challenge for prospective physics teachers. So the importance of conducting workshops to conduct a learning approach using methods of using practicum media by optimizing the surrounding environment such as the use of passive and active electrical component materials. The implementation of this activity is carried out for six hours consisting of 1. Introduction 2. Characterization 3. Implementation. The results of this dedication activity the prospective physics teachers are very enthusiastic because so far the physics candidates are only limited to knowing but do not understand the physical or physical meaning.